Composites reinforced with oriented microplatelets - Zhou, Xiangyu (Nanyang Technological University, 2021)
This report presents the process and outcomes of the final year project A190: composites reinforced with oriented micoplatelets. The inspection of composite microstructure has always been important for exploring material properties. Many methods have been developed to explore the appearance of microstructure using microscopy. In this project, an experimental investigation was conducted to examine the color of composites reinforced with micropletelets using pictures taken by a mobile phone. The experiment conducted used epoxy reinforced with alumina microplatelets controlled by external magnetic field. The color on the surface of the specimen produced, where the microplatelets were aligned, were captured at different angles and evaluated in terms of grayscale. A relationship of color and microplatelets orientation was developed as a result, which could be used to develop a simple method for estimating microstructure orientations.